Modeling effects of trauma and stress on disordered eating and substance abuse: the role of experiential avoidance and meaning in life - Barenz, Jennifer Diane, author; Steger, Michael F., advisor; Conner, Bradley T., committee member; Davalos, Deana B., committee member; Eakman, Aaron M., committee member (Colorado State University. Libraries, 2017)
Traumatic or stressful life events often compel people to avoid internal experiences such as negative thoughts, emotions, and memories. The process of avoiding painful internal stimuli is commonly referred to as experiential avoidance (Hayes et al., 1996; Hayes et al., 2004). While often effective in the short-term, experiential avoidance has been shown to increase risk for behavioral disorders, including disordered eating and substance abuse. Additionally, individuals with eating disorders frequently struggle to establish a coherent sense of meaning and identity (Fox & Leung), indicating that meaning in life is relevant to the study of disordered eating. Structural equation modeling (SEM) analyses were used to explore relationships between traumatic or stressful life events, experiential avoidance, meaning in life, disordered eating, and substance abuse within a multivariate model. SEM analyses revealed a good fit between the proposed structural model and the data present in two large samples of undergraduate students. Individual regression analyses also explored meaning in life and experiential avoidance as predictors of treatment outcomes in a sample of individuals diagnosed with eating disorders.
Keywords: experiential avoidance; stress; trauma; meaning in life; eating disorders; substance abuse